A systematic review and meta-analysis of sex differences in clinical outcomes of hypertrophic cardiomyopathy - Liu, Guyue; Su, Li; Lang, Mingjian (Frontiers in Cardiovascular Medicine, 2023)
This study aimed to systematically review the literature and perform a metaanalysis to comprehensively compare the clinical outcomes between female and male patients with HCM.Methods The primary endpoints examined were: (1) all-cause mortality; (2) an arrhythmic endpoint comprising sudden cardiac death (SCD), sustained ventricular tachycardia, ventricular fibrillation, or aborted SCD; and (3) a composite endpoint incorporating either (1) or ( 2), in addition to hospitalization for heart failure or cardiac transplantation. Baseline characteristics revealed that the female group exhibited an advanced age (55.66 ± 0.04 years vs. 50.38 ± 0.03 years, pooled mean difference [MD] = 0.31, 95% CI: 0.22-0.40, p = 0.000, I 2 = 88.89%), a higher proportion of New York Heart Association class III/IV patients (pooled odds ratio [OR] = 1.94, 95% CI: 1.55-2.43, p = 0.000, I 2 = 85.92%), and a greater prevalence of left ventricular outflow tract gradient greater than or equal to 30mmHg (pooled OR = 1.48, 95% CI: 1.27-1.73, p = 0.000, I 2 = 68.88%) compared to the male group. The female group were more likely to have a positive genetic test (pooled OR = 1.27, 95% CI: 1.08-1.48, p = 0.000, I 2 = 42.74%) and to carry the myosin heavy chain beta 7 mutation (pooled OR = 1.26, 95% CI: 1.04-1.54, p = 0.020, I 2 = 0.00%) compared to the male group. Female sex exhibited a significant association with increased risks of all-cause mortality (pooled OR = 1.62, 95% CI: 1.38-1.89, p = 0.000, I 2 = 72.78%) and the composite endpoint (pooled OR = 1.47, 95% CI: 1.20-1.79, p = 0.000, I 2 = 84.96%), while no substantial difference was observed in the arrhythmic endpoint (pooled OR = 1.08, 95% CI: 0.87-1.34, p = 0.490, I 2 = 55.48%).The present findings suggest that female patients with HCM tend to experience poorer clinical outcomes. It is imperative to critically reevaluate disease definitions and enhance awareness to mitigate delays in the diagnosis and treatment of HCM in women, thereby fostering equitable healthcare practices.